(3eHGOF GdJMdjd GdGbJUGOj GdLRFjs - (3HhSYOI(B, (3SYjOIs ((3GdLRGFQs (3OGQ gheIs, 2016)
(3eaGgje CSGSjI , ebOeI aj GdWdH , GdYQV h GdJhGRf, bjGS GdeQhfGJ(B/(3eQhfI GdYQV h eQhfI GdWdH , JWHjbGJ Ydi JhGRf GdShb , fXQjI GdeSJgdc(B/(3eONd GdefaYI , fXQjI GdeSJgdc(B/(3eONd efMfjGJ GdShGA(B: (3eaghe efMfjGJ GdShGA,GdNjGQ GdCeKd ddeSJgdc , GdJHGOd , efMfi GdGSJgdGc (B- (3GdONd h efMfi EfLd , efMei GdGSJgdGc (B- (3GdSYQ h efMfi WdH GdeSJgdc , aUd GdCKQjf GdEMdGdj h GdONd dJZjjQ GdSYQ , GdMGdGJ GdGSJKfGFjI h JWhQGJ fXQjI GdWdH , Jbjje fXQjI efMfjGJ GdShGAceG Je GdJWQj Gdi fXQjI GdGfJGL (B: (3JMdjd Sdhc GdefJL aj GdCeO GdbUjQ h aj GdeOi GdWhjd h efMfi JhSjY GdGfJGL h JGHY GdGfJGL chH OhZdGSh cPG fXQjI GdJcGdja (B: (3JcGdja GdGfJGL aj GdaJQI bUjQI GdCLd h aj GdaJQI WhjdI GdCeO h eKdhjI GdJcGdja h EjLGO GdJcdaI cOGdI dMLe GdGfJGL defJL Ph OGdI CfJGL ef fhY chH OhZdGSceG Je GdJWQb Gdi JGHY GdGjQGO h fXe GdShb , JhGRf GdefJL aj Xd Shb GdefGaSI GdJGeI , JhGRf GdefJL aj Shb GdGMJcGQ GdJGe , JhGRf GdefJL aj Shb JShOgG GdefGaSI , JhGRf GdefJL aj hb GMJcGQ GdbdI(B.s
Keywords: (3GdGbJUGO GdJMdjdjs; (3GdGbJUGO GdLRFjs